Jananee janmabhoomischa: ICT solutions for pronational digital society - Srihari Rao, N; Chandra Sekharaiah, K; Ananda Rao, A (International Journal of Engineering and Technology, 2018)
Personality Developmentâ€™, â€˜Social Developmentâ€™, â€˜National Developmentâ€™, â€˜National Spiritâ€™, â€˜National Amityâ€™, â€˜Nation Building Characterâ€™, â€˜National Consciousnessâ€™, â€˜National Solidarityâ€™, â€˜National Awarenessâ€™, â€˜National Integrationâ€™, â€˜National Sovereigntyâ€™, â€˜National Integrityâ€™, and â€˜National Unityâ€™ are the diminishing ideas among the citizens of a country now-a-days. Opportunities for cybercrimes worsen this situation further by luring the people with bad motivations, some who justify the cybercrimes somehow and some to perpetrate the cybercrimes. As the public authorities are not capable enough to handle cybercrime cases well as of now or due to lacunae in cyber laws, cyber criminals are evading and sweeping under the carpet. The societal status, may it be progressive or perishable depends on the kind of information that is provided to the people of society. If society is input with right information, the society will progress, develop positively and on the other hand the society will perish with the wrong or garbage information. In this context, Right-To-Information (RTI) Act 2005 plays a vital role by providing â€˜Right Informationâ€™ through â€˜Information Transparencyâ€™. We found out an organization named JNTUHJAC (offline) with its website with URL- www.jntuhjac.com (online) running from so many years, committed three or more cybercrimes against the Union of India. We considered this online and offline organization for our case study and for discussions of our solutions for these cybercrimes. In this paper, we proposed a research methodology based on Information and Communication Technology (ICT) approaches to prevent the conversion of Cybercrime or Ill-Informed Society into Perishable Society and hence hope to succeed in transforming Cybercrime or Ill-Informed Society into Well-Informed Society and hence into a â€œProgressive Society/Knowledge Society/Digital Society.Â Â